Does an inorganic fertilizer subsidy promote the use of organic fertilizers in Nigeria? - Alabi, Reuben Adeolu; Adams, Oshobugie Ojor; Abu, Godwin (International Food Policy Research Institute, 2017)
This study examines the crowding-out or -in effect of organic fertilizers as a result of the inorganic fertilizer subsidy program in Nigeria. The study made use of the Nigeria General Household Survey (GHS) dataset from 2010-2011, which contains 5,000 farmers. We estimate the probability and intensity of organic and inorganic fertilizer use conditioned on the amount of fertilizer subsidy accessed by the farmers using Probit and Tobit IV methodologies. The results reveal that organic fertilizer is being used as an alternative to inorganic fertilizer and that the farmers who are not able to access the fertilizer subsidy rely on organic fertilizer. Apart from revealing the crowding-out effect of the fertilizer subsidy on the use of organic fertilizers, our findings also bring to the fore the role that transportation and regional constraints play in stimulating inorganic fertilizer application among farmers outside the fertilizer subsidy scheme. We conclude with some recommendations on how to increase organic fertilizer use and promote integrated soil fertility management among farmers in Nigeria.